Attenuation of SARS‐CoV‐2 replication and associated inflammation by concomitant targeting of viral and host cap 2'‐O‐ribose methyltransferases. (25th July 2022) - Bergant, Valter; Yamada, Shintaro; Grass, Vincent; Tsukamoto, Yuta; Lavacca, Teresa; Krey, Karsten; Mühlhofer, Maria‐Teresa; Wittmann, Sabine; Ensser, Armin; Herrmann, Alexandra; vom Hemdt, Anja; Tomita, Yuriko; et al.
Abstract: The SARS‐CoV‐2 infection cycle is a multistage process that relies on functional interactions between the host and the pathogen. Here, we repurposed antiviral drugs against both viral and host enzymes to pharmaceutically block methylation of the viral RNA 2'‐O‐ribose cap needed for viral immune escape. We find that the host cap 2'‐O‐ribose methyltransferase MTr1 can compensate for loss of viral NSP16 methyltransferase in facilitating virus replication. Concomitant inhibition of MTr1 and NSP16 efficiently suppresses SARS‐CoV‐2 replication. Using in silico target‐based drug screening, we identify a bispecific MTr1/NSP16 inhibitor with anti‐SARS‐CoV‐2 activity in vitro and in vivo but with unfavorable side effects. We further show antiviral activity of inhibitors that target independent stages of the host SAM cycle providing the methyltransferase co‐substrate. In particular, the adenosylhomocysteinase (AHCY) inhibitor DZNep is antiviral in in vitro, in ex vivo, and in a mouse infection model and synergizes with existing COVID‐19 treatments. Moreover, DZNep exhibits a strong immunomodulatory effect curbing infection‐induced hyperinflammation and reduces lung fibrosis markers ex vivo . Thus, multispecific and metabolic MTase inhibitors constitute yet unexplored treatment options against COVID‐19. Synopsis: A target‐based drug repurposing approach to inhibit SAM‐dependent methyltransferases (Mtases) shows that the host MTase MTr1 can compensate for loss of the viral encoded NSP16 MTase. Targeting both MTr1 and NSP16 is needed to suppress SARS‐CoV‐2 replication. Host 2'‐O‐ribose methyltransferase MTr1 is a novel host factor of SARS‐CoV‐2 and compensates for the loss of NSP16. Concomitant inhibition of MTr1 and NSP16 is required to efficiently suppress SARS‐CoV‐2 replication. Target‐based drug repurposing identified a bispecific MTr1/NSP16 inhibitor tubercidin, which is highly antiviral against SARS‐CoV‐2. Host‐directed SAM‐cycle inhibitors, exerting indirect broad spectrum methyltransferase inhibition, are potent antivirals against SARS‐CoV‐2 with additional immunomodulatory and fibrosis‐curbing functions. Abstract : A target‐based drug repurposing approach shows that inhibition of both host and viral SAM‐dependent methyltransferases is needed to block SARS‐CoV‐2 cap 2'‐O‐ribose methylation and to suppress SARS‐CoV‐2 replication.